Multidisciplinary approach to functional somatic syndromes: study protocol for a population-based prospective cohort study - Hamidreza Roohafza; Harold Snieder; Fatemeh Hadizadeh; Peyman Adibi; Alireza Ani; Ahmad Vaez (BMJ Open)
Introduction Isfahan functional disorders (ISFUN) cohort study aims to describe the interplay of genetic and environmental factors in shaping the characteristics of functional somatic syndromes (FSS). This study is primarily intended to investigate the epidemiology, risk factors, course and prognosis of FSSs in a sample of adult Iranian population. The other aim is to develop a new delimitation of FSSs based on an integrated multidisciplinary approach comprising of phenotypic and multiomics data.Methods and analysis ISFUN is a population-based prospective cohort study designed to follow a population of randomly selected seemingly healthy adults (18–65 years) through annual visits during a 4-year observation period. Structured questionnaires are used for data collection and clinical assessment of the participants. Questionnaire-based diagnosis of FSSs are validated in a medical interview. Human DNA genotyping, microbial amplicon sequencing and urine analysis is under progress for genomics, microbiota and metabolomics profiling, respectively. Enrolment began in September 2017, and study completion is expected in 2022. A total number of 1943 participants were initially recruited.Ethics and dissemination Ethical approval for data collection was granted by the National Research Ethics Committee of the Iranian Ministry of Health and Medical Education and the Research Ethics Committee of Isfahan University of Medical Sciences (IR.MUI.REC.1395.1.149). Following the description of the study procedure, we obtained written informed consent from all study participants. Study findings will be disseminated through peer-reviewed publications and presentations at scientific meetings.